Hope for the future, ingroup threat and perceived legitimacy in three healthcare professional groups - Sollami, Alfonso; Caricati, Luca (Acta Biomedica Atenei Parmensis, 2018)
Background and aims of the work: All societies are organised as hierarchies based on prestige or status. Similarly, healthcare organizations (as well as many other types of organization) are composed by professional hierarchies in which some professional groups are powerful and higher in status and other groups are powerless and lower in status. This research investigated the effects of social status and hope for future group advancement on perceptions of social identity threat and legitimacy of social stratification. Physicians (the dominant professional group), nurses and healthcare operators (the dominated professional groups) were led to believe that professional stratification would change in the future, but that the nature of the change was unforeseeable. Method: A quantitative study was conducted, proposing to the participants an instrument consisting of a series of validated questionnaires for the measurement of: group status, Ingroup threat, hope for future ingroup improvement, legitimacy of the professional hierarchy and Check for status differences. Results: The results indicate that in the context of social instability, the dominant group perceived greater ingroup threat than the dominated groups. Hope for future advancement was negatively associated with perception of ingroup threat, regardless of group membership. Perception of ingroup threat was negatively associated with the perceived legitimacy of social stratification. Finally, perceived threat mediated the relationship between group status and perceived legitimacy. These results support social identity theory’s contention that the legitimacy of social stratification is linked to social identity needs such as avoidance of ingroup threat.